1998
DOI: 10.1038/sj.bjp.0701681
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prolonged treatment with imipramine on the biosynthesis and functional characteristics of D2 dopamine receptors in the rat caudate putamen

Abstract: 1 The present study shows the eects of imipramine in a single dose (10 mg kg 71 , p.o.) or following repeated (14 days, twice a day) treatment on the level of mRNA coding for D 2 dopamine receptors in the rat caudate putamen (CP). Repeated administration of imipramine resulted in the increase of the level of mRNA coding for D 2 dopamine receptors. 2 Radioligand binding studies with the D 2 receptor agonist, [3 H]-N-0437, indicated, that following imipramine administration, the anity of the agonist for the D 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
1
2
1
Order By: Relevance
“…In addition to the changes reported in the present studies, the NET À/À mice have been shown to be supersensitive to psychostimulants (Xu et al, 2000), a phenomenon that has been also observed following the repeated treatment with antidepressants (DziedzickaWasylewska and Rogoz ' , 1998;Maj et al, 1984;Rogoz ' and Dziedzicka-Wasylewska, 1999). More biochemical studies are necessary to elucidate further molecular mechanisms underlying these changes.…”
Section: Discussionsupporting
confidence: 66%
“…In addition to the changes reported in the present studies, the NET À/À mice have been shown to be supersensitive to psychostimulants (Xu et al, 2000), a phenomenon that has been also observed following the repeated treatment with antidepressants (DziedzickaWasylewska and Rogoz ' , 1998;Maj et al, 1984;Rogoz ' and Dziedzicka-Wasylewska, 1999). More biochemical studies are necessary to elucidate further molecular mechanisms underlying these changes.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, previous studies have reported that imipramine up-regulates DRD2 expression in the striatum (5,6), but no significant changes were observed in our study (Fig. 1).…”
contrasting
confidence: 50%
“…On the other hand, hypoxia is reported to serve as a factor in the upregulation of β-AR [33], so that the hypoxic environment in HCC may lead to functional alterations in intracellular signal transduction systems which indeed are associated with receptor upregulation [34,35,36]. …”
Section: Discussionmentioning
confidence: 99%